2021
DOI: 10.3390/diagnostics12010005
|View full text |Cite
|
Sign up to set email alerts
|

Endorectal Ultrasonography and Pelvic Magnetic Resonance Imaging Show Similar Diagnostic Accuracy in Local Staging of Rectal Cancer: An Update Systematic Review and Meta-Analysis

Abstract: Background: Endorectal Ultrasonography (EUS-ERUS) and pelvic magnetic resonance imaging (MRI) are world-wide performed for the local staging of rectal cancer (RC), but no clear consensus on their indications is present, there being literature in support of both. The aim of this meta-analysis is to give an update regarding the diagnostic test accuracy of ERUS and pelvic MRI about the local staging of RC. Materials and methods: A systematic literature search from November 2020 to October 2021 was performed to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
1
5
0
2
Order By: Relevance
“…The ERUS T category assessment also performed well, and it is important to keep in mind that this study was performed in a clinical setting where the operators were not blinded; therefore, the T stage assessment, as well as the SWE measurement, may be subject to bias. We also showed that ERUS performed with a slightly higher accuracy than MRI in patients with early rectal cancer, which is similar to previous findings [ 21 ]; however, MRI is superior in advanced rectal cancer and provides specific imaging features related to tumor aggressiveness such as lymph node staging, MR circumferential resection margin involvement, and extramural vascular invasion [ 22 ]. It may be noted that MRI overstaged 13% of tumors (11/83), including 10% of adenomas, whereas ERUS only overstaged 5% of the tumors (4/86), including 5% of the adenomas (3/62).…”
Section: Discussionsupporting
confidence: 89%
“…The ERUS T category assessment also performed well, and it is important to keep in mind that this study was performed in a clinical setting where the operators were not blinded; therefore, the T stage assessment, as well as the SWE measurement, may be subject to bias. We also showed that ERUS performed with a slightly higher accuracy than MRI in patients with early rectal cancer, which is similar to previous findings [ 21 ]; however, MRI is superior in advanced rectal cancer and provides specific imaging features related to tumor aggressiveness such as lymph node staging, MR circumferential resection margin involvement, and extramural vascular invasion [ 22 ]. It may be noted that MRI overstaged 13% of tumors (11/83), including 10% of adenomas, whereas ERUS only overstaged 5% of the tumors (4/86), including 5% of the adenomas (3/62).…”
Section: Discussionsupporting
confidence: 89%
“…ERUS also outperforms MRI in advanced T3 tumors as reported by Chan et al due to a higher sensitivity for small lesion and a better visualization of thin layers such as the serosa [37]. For the evaluation of nodal involvement, different meta-analyses suggest a similar or slightly more accurate nodal staging with ERUS with respect to MRI [36,37]. Contrast-enhanced endoscopic ultrasound (CE-EUS) is not routinely performed in evaluation and local staging of rectal cancer; however, in a small case series by Gibiino et al including 12 rectal lesions, CE-EUS staging provided useful information regarding either the integrity of the muscular layer and the presence of vascularization, which are both factors known to be predictive of non-curative endoscopic resection; CE-EUS staging corresponded to the final pathological stages in 9/12 (75%) lesions, improving the distinction between T1 and T2 lesions [38].…”
Section: Erusmentioning
confidence: 87%
“…ERUS must be performed by expert clinicians since it is a highly operator-dependent technique. In a recent meta-analysis by Luglio G. et al, ERUS outperformed MRI in all T stages except T4, with remarkable difference in T1 tumors; T4 rectal cancer can benefit from MRI, which, at this stage, is connoted by higher sensitivity and slightly lower specificity [36]. ERUS also outperforms MRI in advanced T3 tumors as reported by Chan et al due to a higher sensitivity for small lesion and a better visualization of thin layers such as the serosa [37].…”
Section: Erusmentioning
confidence: 96%
“…The preoperative clinical staging of rectal cancer is primarily conducted by MRI and ERUS. 10,11 Although ERUS is the ideal staging approach for early tumors, MRI is really thought to be the most effective rectal cancer staging imaging method. The cancer diagnosis and treatment regulations under the NCCN guidelines (2022 edition) use ERUS as an alternative examination for the preoperative staging and diagnosis of low and middle rectal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed and accurate preoperative staging helps surgeons know about the extent of tumor invasion so as to develop the most effective treatment plans for patients and improve treatment outcomes. The preoperative clinical staging of rectal cancer is primarily conducted by MRI and ERUS 10,11 . Although ERUS is the ideal staging approach for early tumors, MRI is really thought to be the most effective rectal cancer staging imaging method 12,13 .…”
Section: Discussionmentioning
confidence: 99%